Watching the Detectives - Bell, Ian F. A. author. aut Link
XV, 193 p.
Keywords: In this collection of essays, a number of critics offer commentary on the crime fiction genre, exploring the kinds of pleasure it offers. Looking under the attractive surface of these books, the contributors discover a number of complex issues.